Pemanfaatan Canva, Crossword dan Assemblr Edu dalam Pembuatan Media Pembelajaran Berbasis Teknologi - Kumala, Siti Ayu; Sumarni, Ria Asep (Lembaga Pengembangan Kinerja Dosen, 2025)
In today's digital era, teachers are faced with increasingly greater learning challenges. The ability to create interesting, innovative and creative learning media must be possessed by teachers at all levels of education. However, not all teachers have the facilities to learn hpw to create learning media. Various tools and applications have been developed to support the learning process. Some of these applications are Canva, crossword puzzle and Assemblr Edu. These three applications are very helpful in creating learning media to attract students' interest in learning. Community service activities have been carried out at SDN 01 Duren Seribu which is located in Depok City, West Java. The activities carried out were in the form of training in creating learning media by utilizing the Canva, crossword and Assemblr Edu applications for teachers of SDN Duren Seribu 01. The teachers were asked to practice directly creating learning media according to their respective subject areas. After this training, the teachers stated that this training was very useful and made them more proficient in the application in creating learning media so that they could create interesting and creative learning media